Fluxo de Processamento de Imagens para Respostas Rápidas a Desastres Naturais - Rocha, Brenda Oliveira; Alves, Larissa Mioni Vieira [UNESP]; de Oliveira, Alisson Cleiton; de Moraes Costa, Cesar Augusto; Körting, Thales Sehn (My University, 2023)
This paper describes a methodological process for developing an image processing flow using the Python language for rapid analysis of areas affected by landslides and floods. Considering the need for rapid provision of maps to disaster management processes, several Digital Image Processing (DIP) techniques were organized, considering the possibility of generating new products and new interpretations in the face of complex scenarios of areas affected by extreme events.